Polyploid GWAS reveals the basis of molecular marker development for complex breeding traits including starch content in the storage roots of sweet potato - Haque, Emdadul; Shirasawa, Kenta; Suematsu, Keisuke; Tabuchi, Hiroaki; Isobe, Sachiko; Tanaka, Masaru (Frontiers in Plant Science, 2023)
Given the priority on genome-based breeding of sweetpotato enabling promotion of food and nutritional security in the upcoming human society, here we aimed to dissect the genetic basis of storage root starch content (SC) when associated with a complex set of breeding traits including dry-matter (DM) rate, storage root fresh weight (SRFW) and anthocyanin (AN) content in a mapping population containing purple-fleshed sweetpotato. A polyploid GWAS was extensively exploited using 90, 222 SNPs obtained from a bi-parental 204 F1 population between ‘Konaishin’ having high SC but no AN and ‘Akemurasaki’ having high AN content but moderate SC. Through the comparison of polyploid GWAS on whole set of 204 F1, 93 high AN containing F1 and 111 low AN containing F1 populations, a total of two (consists of 6 SNPs), two (14 SNPs), four (8 SNPs) and nine (214 SNPs) significantly associated signals were identified for the variations of SC, DM, SRFW and the relative AN content, respectively. Of them, a novel signal associated with SC, which was most consistent over year 2019 and 2020 in both 204 F1 and 111 low AN containing F1 populations, was identified on the homologous group 15. The 5 SNP markers associated in homologous group 15 could affect SC improvement with a degree of positive effect (~4.33) and screen high starch containing lines with higher efficiency (~68%). In a database search of 62 genes involved in starch metabolism, 5 genes including enzyme genes granule-bound starch synthase I (IbGBSSI), α-amylase 1D, α-amylase 1E and α-amylase 3 and one transporter gene ATP/ADP-transporter were located on homologous group 15. In an extensive qRT-PCR of these genes using the storage roots harvested at 2, 3 and 4 months after field transplantation in 2022, IbGBSSI, which encodes the starch synthase isozyme that catalyze the biosynthesis of amylose molecule, was most consistently elevated during starch accumulation in sweetpotato. These results would enhance our understanding of the underlying genetic basis of a complex set of breeding traits in the starchy roots of sweetpotato, and the molecular information, particularly for SC, would be a potential platform for molecular marker development for this trait.